Swimming Training Mitigates Neurological Impairment of Intracerebral Haemorrhage in Mice via the Serine-Threonine Kinase/Glycogen Synthase Kinase 3β Signalling Pathway. (1st October 2022) - Li, Yongxu; Lu, Taotao; Wei, Wei; Lin, Zhicheng; Ding, Linlin; Li, Zhaohui; Xue, Xiehua
Graphical abstract: Highlights: ST intervention attenuated the neurological deficits and the behavioral manifestation of ICH mice. ST improved the brain metabolites of perihematoma in ICH mice according to magnetic resonance spectroscopy. The neuroprotection of ST was related to the inhibition of glial activation and the apoptosis in the ICH mice. ST displayed the neuroprotection through activating the Akt/GSK3β pathway in the ICH mice. Abstract: Swimming training (ST) can mitigate functional disorders in neurological diseases, but the effect and mechanism of ST in improving the neurological function of intracerebral haemorrhage (ICH) have not been reported. Our study aimed to explore the protective effect of early ST on ICH mice and its relationship with the serine-threonine kinase (Akt)/glycogen synthase kinase 3β (GSK3β) pathway. Our findings showed that the ICH model mice had poor behavioural manifestations in the Y maze test and open field test compared to the ST group and sham group. The modified neurological severity score was increased in the ICH mice, and 7 days of ST intervention significantly attenuated the neurological deficits. The ratios of myo-inositol/creatine, lactate/creatine and glutamate/creatine were decreased, and the ratios of N-acetylaspartate/creatine and choline/creatine were increased in the ICH mice with ST intervention. ST intervention decreased the expression of Iba1 and GFAP. Seven days of ST significantly increased the expression of p-Akt/Akt compared to that in the ICH mice. Furthermore, the Akt kinase inhibitor GSK690693 exacerbated neurological impairment, increased the expression of Iba1, GFAP and Bax/Bcl-2, and reversed the anti-apoptotic effects and anti-glia activation of ST, which was associated with the inhibition of p-Akt/Akt and p-GSK3β/GSK3β expression. These results indicated that the protective role of ST in ICH was mediated via the Akt/GSK3β pathway. In conclusion, ST displayed neuroprotection by inhibiting apoptosis and glial activation in ICH mice by activating the Akt/GSK3β signalling pathway.